(untitled) (Islas, 2021)
The work is an approach and recognition of an outstanding personality from Camagüey, María Montejo Tan who consecrated her life en favour of the infancy of her Camagüey. At the beginning of the 20th Century, due to her personal effort, shoe created a beneficent institution for orphan girls the asylum Amparo de la Niñez. This way she helped those orphan girls to have a better and happier future in a society in which discrimination and lack of attention to children’s right characterized that epoch. This woman wrote one of the most beautiful story of love and solidarity in the history of Camagüey. The main purpose of this article is to divulge about the life and work of an almost unknown personality by the people from Camagüey. Her work constitutes an antecedent of homes for children without filial protection created after the triumph of the Revolution.